â€œPengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umumâ€ Pembebasan Lahan Pembangunan Jalur Ganda Rel Kereta Api Pekalongan â€“ Semarang Di Kota Pekalongan - S, Tegar Harry; ., Fitriyah; Widayati, Wiwik (Journal of Politic and Government Studies, 2013)
Steps to fix the railway line in Indonesia started. The plan, traffic lane north of the islandof Javawill be made into a double rail line. The rail track distance is 400 kilometers.Infrastructure development, the government has a plan to fix the railway line in Indonesia. Theplan, traffic lane north of the island of Java will be made into a double rail line. The rail trackdistance is approximately 436 kilometers. Double track railway will be undertakensimultaneously.The existence of double track railway will quickly push the national economy. Not onlythat, the burden of capital in the form of ground transportation vehicle that is felt during thisalready saturated, will be helped and can be reduced in the presence of a double track railway.Project construction of double track railway is expected to require a lot of manpower. Inaddition, there will be an increased flow of trucks carrying material on the Northern line ofJava, being up to 800 units per day, especially on a track Cirebon-Surabaya. By working inunison, the estimated future rail construction is completed in 2013. Expected in 2014, the doubletrack railway will be operational.In the implementation of the construction of double track railway line, of course, it takesquite a bit of land for this purpose, thus a need for cooperation between the Ministry ofTransportation Directorate General of Railways with the Local Government and Land Office torelease land for the construction of double track railway traffic Pekalongan - Semarangparticularly in the area of Pekalongan. As for exercising land acquisition is governed byPresidential Decree No. 36 of 2005 as amended in Presidential Regulation No. 65 of 2006.Keywords: Land acquisition Double Line Railway, Local Government, Land AcquisitionCommittee (P2T), and Output